2010
DOI: 10.1016/j.jcrs.2010.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Improving the prediction accuracy of the SRK/T formula: The T2 formula

Abstract: The SRK/T formula has nonphysiologic behavior that contributes to IOL power prediction errors. A modification to the formula algorithm, the T2 formula, can be directly substituted for SRK/T, resulting in significantly improved prediction accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 4 publications
1
72
0
6
Order By: Relevance
“…In our case, we chose the rigid PMMA model 6.0 mm optic because the subluxated IOL had to be explanted. Using the A constant for the negative-powered IOLs, according to the modified SRK/T formula (ie, SRK/ T2), 7 we obtained an SE approaching emmetropia. In addition to published results for iris-claw IOLs, the iris-claw myopic IOL is a good alternative to avoid the expected hyperopic refractive result when an IOL must be explanted due to IOL dislocation.…”
Section: Discussionmentioning
confidence: 96%
“…In our case, we chose the rigid PMMA model 6.0 mm optic because the subluxated IOL had to be explanted. Using the A constant for the negative-powered IOLs, according to the modified SRK/T formula (ie, SRK/ T2), 7 we obtained an SE approaching emmetropia. In addition to published results for iris-claw IOLs, the iris-claw myopic IOL is a good alternative to avoid the expected hyperopic refractive result when an IOL must be explanted due to IOL dislocation.…”
Section: Discussionmentioning
confidence: 96%
“…26 The Haigis formula is reported to give accurate predictions for both short 27 and long eyes, 28 but Olsen's formula may produce results slightly better than Haigis'. 29 The Holladay 2 formula is suggested to be 'one of the more accurate formulas available', 8 but there is little systematic evidence for this assertion.…”
Section: Formula Choicementioning
confidence: 99%
“…The individual steps of the SRK/T formula were examined with reference to a database of biometry and refractive outcomes in 11.189 eyes by Sheard et al[5*] They observed a nonphysiologic behavior in the calculation of corrected axial length and corneal height. They developed the T2 formula using a regression formula for corneal height derived from the development subset and they concluded that any surgeon who uses the SRK/T formula could switch to using the T2 formula and improve refractive outcomes by 10%.…”
Section: Intraocular Lens Power Calculationmentioning
confidence: 99%
“…Numerous devices and formulas are currently available, allowing accurate determination of the IOL power needed to reach the target refraction. [13,4**,5*,69,10*,1116, 17*18] In order to accomplish target refraction, axial length (AL), anterior chamber depth (ACD), and corneal radii (K1and K2) need to be accurately measured. Moreover, proper choices of IOL power calculation formulas are important, as are the use of accurate IOL constants, depending on the type of IOL and post-operative IOL location.…”
Section: Introductionmentioning
confidence: 99%